DINAMIKA KONFLIK SYIAH: AKAR HISTORIS, GEOPOLITIK KONTEMPORER, DAN UPAYA REKONSILIASI - Muhammad Munzir Azyumardi; Nurlaelah Abbas; Indo Santalia (J-Alif : Jurnal Penelitian Hukum Ekonomi Syariah dan Budaya Islam, 2025)
The conflict between Shia and Sunni Islam has deep historical roots, originating from the succession dispute following the death of Prophet Muhammad. The events at Saqifah and the contested role of Ali ibn Abi Talib marked the beginning of political divergence that eventually evolved into theological conflict, particularly through the Shia doctrine of Imamah, which stands in contrast to the Sunni concept of the caliphate. Over time, these differences solidified into distinct sectarian identities and have contributed to ongoing tensions, especially in the geopolitical sphere after the 1979 Islamic Revolution in Iran. Contemporary crises in Iraq, Syria, and Yemen illustrate how sectarian sentiments are often exploited for political purposes. Nevertheless, various reconciliation efforts have emerged, including the Amman Message and other inter-sectarian dialogues. This article aims to trace the historical origins of the Shia–Sunni conflict, analyze its contemporary geopolitical implications, and evaluate the challenges and prospects for peaceful coexistence within the Muslim world.